2022
DOI: 10.1021/acs.orglett.2c00516
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of DNA-Tagged Alkenes with Diazo Compounds via Photocatalysis

Abstract: To explore potential chemical space using DNA-encoded library (DEL) technology, the development of various types of robust DNA-compatible reactions is urgently needed. Diazo compounds, which serve as valuable building blocks and important synthons in synthetic chemistry, have been rarely applied in DEL synthesis, probably because of their potential modifications of the bases and phosphate backbone of DNA. Herein we report two cases of DNA-compatible reactions with alkenes and diazo compounds, providing corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 39 publications
0
19
0
1
Order By: Relevance
“…Hantzsch ester (HE) has been well-applied in photoredox reactions as terminal reductants affording a hydride, electron, and hydrogen atom . HE is readily available and high stability; thus, it could be an ideal reagent as a sacrificial single-electron donor and hydrogen atom donor during the conversion of diazo compounds to carbon radical species . In 2020, Doyle and co-authors reported an elegant photocatalytic radical reaction of diazo compounds with alkenes in the presence of HE .…”
mentioning
confidence: 99%
“…Hantzsch ester (HE) has been well-applied in photoredox reactions as terminal reductants affording a hydride, electron, and hydrogen atom . HE is readily available and high stability; thus, it could be an ideal reagent as a sacrificial single-electron donor and hydrogen atom donor during the conversion of diazo compounds to carbon radical species . In 2020, Doyle and co-authors reported an elegant photocatalytic radical reaction of diazo compounds with alkenes in the presence of HE .…”
mentioning
confidence: 99%
“…As a result, reactions carried out under conventional heating conditions with low or high pH are limited for the preparation of DNA-conjugated compounds. Moreover, because negative charges of phosphates in the DNA backbone exhibit a metal-chelation effect, the application of recently developed transition metal catalysis is problematic. , For this reason, the development of a reaction for constructing a DNA-encoded library (DEL) capable of introducing a novel functional group is required to extend the versatility of current technologies. …”
mentioning
confidence: 99%
“…25–30 While DNA liability to stringent conditions hampers its application in conventional organic synthesis, 31,32 a variety of DNA-compatible reactions have still been successfully developed in recent years to expand the structural complexity of encoded chemical libraries. 33–40…”
mentioning
confidence: 99%
“…[25][26][27][28][29][30] While DNA liability to stringent conditions hampers its application in conventional organic synthesis, 31,32 a variety of DNA-compatible reactions have still been successfully developed in recent years to expand the structural complexity of encoded chemical libraries. [33][34][35][36][37][38][39][40] Diversity-oriented synthesis (DOS) represents a fast approach for generating distinct structures based on the uniform intermediate, which is in accordance with the DEL concept. [41][42][43] More structural diversity would undoubtedly increase the chemical space and broaden the structural complexity of the library.…”
mentioning
confidence: 99%